2023
DOI: 10.1021/acs.jpclett.2c03701
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-Level Instability as a Way to Tailor the Properties of La3Te4

Abstract: Traditionally, the formation of off-stoichiometric compounds is believed to be the growth effect rather than the intrinsic tendency of the system. However, here, using the example of La 3 Te 4 , we demonstrate that in n-type gapped metals having a large internal gap between principal band edges and the Fermi level inside of the principal conduction band, Fermi-level instability can develop, resulting in a decrease in the formation energy for acceptor defects. Specifically, La vacancies in La 3 Te 4 form sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…1a) can develop off-stoichiometry due to the decay of conduction electrons to the acceptor level (known as Fermi level instability). 9,14,24 Such behavior can lead to the formation of a range of non-stoichiometric compounds due to the intrinsic non-thermal tendency of the system, even at low temperatures. For instance, previous experimental works 25,26 and our recent first-principles calculations 24 showed that La 3 Te 4 (I% 43d, No.…”
Section: Gapped Metals As Examples Of Optoelectronic and Plasmonic Ma...mentioning
confidence: 99%
See 3 more Smart Citations
“…1a) can develop off-stoichiometry due to the decay of conduction electrons to the acceptor level (known as Fermi level instability). 9,14,24 Such behavior can lead to the formation of a range of non-stoichiometric compounds due to the intrinsic non-thermal tendency of the system, even at low temperatures. For instance, previous experimental works 25,26 and our recent first-principles calculations 24 showed that La 3 Te 4 (I% 43d, No.…”
Section: Gapped Metals As Examples Of Optoelectronic and Plasmonic Ma...mentioning
confidence: 99%
“…This approach does not introduce any additional charge to the system upon the removal of a La atom. Interestingly, due to the presence of conduction band electrons, the defect formation energy for these vacancies is negative, 24 and the formation of La vacancies increases the thermodynamic stability of the compound even at low temperature. We then conducted DFT calculations on each unique system resulting from at least 40 different randomly selected atomic configurations for each composition.…”
Section: Generation Of Off-stoichiometric Compounds and Defect Calcul...mentioning
confidence: 99%
See 2 more Smart Citations